Analisis Efektifitas Penyaluran Dana Zakat Melalui Program Pemberdayaan Mustahik pada UPZ BAZNAS PT Petrokimia Gresik - Dwi Nursafitri Muchlis, Devy; Dwi Setyaningsih, Nina (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
The mustahik empowerment program is a form of effort made by the Indonesian government in maintaining the potential of zakat in order to improve economic conditions, and one's survival. However, in reality, the potential of zakat in Indonesia has not been maximized. In order for the potential of zakat to be utilized properly, effective management and distribution of zakat funds are needed. This research aims to find out, analyze, and explain how the effectiveness of the distribution of zakat funds carried out by UPZ BAZNAS PT Petrokimia Gresik through mustahik empowerment programs that are run. This research uses qualitative research with a descriptive approach. The data used are primary data, namely the results of direct interviews with related parties, as well as secondary data, namely reports on the distribution of zakat funds for each program run by UPZ BAZNAS PT Petrokimia Gresik, as well as books, journals, and articles related to the title of this research. The results showed that the main purpose of the distribution of zakat funds through mustahik empowerment programs run by UPZ BAZNAS PT Petrokimia Gresik has achieved its main objectives, namely to prosper the lives of mustahik, support the mustahik's economy to be better and minimize the poverty rate in Gresik Regency. The distribution of zakat funds through this mustahik empowerment program can also be said to be effective.